Comparing Nissen Rossetti and Floppy Nissen Techniques in Laparoscopic Reflux Surgery: A Systematic Review and Meta-Analysis - Husna Irfan Thalib (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Gastroesophageal reflux disease (GERD) is one of the most prevalent disorders globally, affecting approximately 13.98% of the adult population. The predominant cause is the dysfunction of the lower oesophagal sphincter (LES). GERD commonly presents with symptoms such as heartburn, regurgitation, and dysphagia. Initial treatment often involves lifestyle modifications and proton pump inhibitors (PPIs). However, surgical intervention becomes necessary for many patients to achieve symptomatic relief. Laparoscopic Nissen fundoplication is the gold-standard surgical treatment for GERD. Despite its widespread use, a debate persists regarding the optimal surgical technique between the Nissen-Rossetti and Floppy Nissen procedures. Objectives: This study systematically evaluates and compares the Nissen-Rossetti and Floppy Nissen fundoplication techniques to determine which provides the best surgical approach for GERD. The objectives include analysing differences in operative parameters, post-operative complications, long-term symptom resolution, and quality of life outcomes. Methodology: A systematic review and meta-analysis were conducted, adhering to PRISMA guidelines. Databases including PubMed, Ovid Medline, Ovid Cochrane, and Scopus were comprehensively searched. Studies reporting demographic characteristics, operative outcomes, complications, and symptoms were included. Data were screened, extracted, and assessed for quality using the Cochrane RoB 2 tool for randomised controlled trials and MINORS for non-randomised studies. Statistical analysis was performed using random- and fixed-effects models via Review Manager (RevMan). Results: Twelve studies involving 1,165 patients met the inclusion criteria. Among these, 320 patients underwent the Nissen-Rossetti procedure, while 600 had the Floppy Nissen procedure. The Nissen-Rossetti technique demonstrated a significantly shorter operative time (mean difference -25.29 minutes, p < 0.00001). However, it was associated with higher rates of postoperative oesophagal dilation (16.3% vs. 4.4%; odds ratio [OR] 3.58, p = 0.0002) and dysphagia (25.1% vs. 15.6%; OR 1.87, p = 0.009). In contrast, the Floppy Nissen procedure resulted in shorter postoperative hospital stays (mean difference -0.18 days, p = 0.01). Symptom resolution rates, including relief from heartburn and regurgitation, were comparable between the techniques. Rates of reoperation and major adverse events showed no significant differences. Conclusions: The Nissen-Rossetti technique offers shorter operative times but is associated with higher rates of dysphagia and oesophagal dilation. The Floppy Nissen procedure, although requiring longer operative times, demonstrated better postoperative outcomes with fewer complications and shorter hospital stays. These findings support the Floppy Nissen as the preferred surgical approach for GERD. Future randomised controlled trials are needed to confirm these results and strengthen clinical recommendations.